OPTIMALISASI LINGKUNGAN PENDIDIKAN DI TENGAH PANDEMI COVID-19 - Isnawati Nur Afifah Latif (PREMIERE : Journal of Islamic Elementary Education, 2020)
The result of students development depends on education received from any it experienced environtmental education. The third environment called “triplecenter of education” can be explained as family, school, and people society. To get the best result from family education , teachers must concern on a couple of rules: 1) Attempt well-circumstance on the family environment; (2) Each family members should learn to hold on each their due and responsibility; (3) Parents and another adults on a family should know each character of the kids on their family; (4) We should keep away from anything destruct the development of children soul; and (5) Let our kids associate with their friends on the same age in the family environment. When kids growing up, they will be an member of people society who has each diversity. School environment is the next destination after kids passing through from family environment to complete the children education process. Teacher on the school not only have an responsibility to educate, but also to improve the cognitive, psychomotor, and affective aspect of the students. After passing through school environment, the education process next to social education in the people society environment. People society means a bunch of many families which have each different rules on it. When we was young, we only have due only, but since we growing as adults, we have wider responsibility on our hands begin from responsibility on our family, on our daily task in the school, people society, until our task on country and God. The emergence of Covid-19 pandemic has an effect on education system and force us to do “learning from home”, it should adapt to government rules to prevent the speread of pandemic. Learning from home system needs “triplecenter of education” to keep education goals can be fully achieved.